P1235 Immunologic impact of chemoradiation in cervical cancer and how immune cell infiltration could lead towards personalized treatment. (1st November 2019) - Lippens, L; Van Bockstal, M; De Jaeghere, EA; Tummers, P; Makar, A; De Geyter, S; Van de Vijver, K; Hendrix, A; Vandecasteele, K; Denys, H
Abstract : Introduction/Background: We investigated the potential of tumour-infiltrating immune cells in pre- and post-treatment tissue specimens and their changes during treatment as predictive or prognostic biomarkers for cervical cancer patients. Methodology: Cervical cancer patients treated with (chemo)radiotherapy and subsequent surgery were included in the current study. Pre- and post-treatment specimens were retrospectively analysed via immunohistochemistry. Immune cell markers for T cells (CD3, CD4, CD8, and FoxP3), macrophages (CD68 and CD163), and B cells (CD20), as well as interleukin-33 (IL33) and (programmed death-ligand 1 (PD-L1), were analysed. Patients were grouped in the low score or high score group based on the amount of positive cells on immunohistochemistry. Correlations to pathological complete response (pCR), cause-specific survival (CSS), and metastasis development during follow-up were evaluated. Results: In total, 38 patients were included. In analysis of pre-treatment biopsies, significantly more pCR was seen for patients with CD8=CD3, CD8≥CD4, positive IL33 tumour cell (TC) scores, IL33 immune cell (IC)<TC, and PD-L1 TC≥5%. Besides patients with high CD8 scores, also patients with CD8≥CD4, CD163≥CD68, or PD-L1 IC≥5% had better CSS. In analysis of post-treatment specimens, less pCR was observed for patients with high CD8 or CD163 scores. Patients with decreasing CD8 or CD163 scores between pre- and post-treatment samples showed more pCR, whereas those with increasing CD8 or decreasing IL33 IC scores showed a worse CSS. Meanwhile, patients with an increasing CD3 score or stable/increasing PD-L1 IC score showed more metastasis during follow-up (figure 1). Conclusion: The intratumoural immune cell landscape is a tool for prediction of outcome and response to (chemo)radiation. Disclosure: This research was supported by a research grant obtained from Roche. E.A.D. received funding from Fonds Wetenschappelijk Onderzoek (FWO) and K.V. received funding from Stichting tegen Kanker.